A review and survey of Problem-Based Learning application in Engineering Education - Abu Hassan, Mohd. Ariffin; Mohd. Yusof, Khairiyah; Abd Hamid, Mohd. Kamaruddin; Hassim, Mimi Haryani; Abdul Aziz, Azila; Syed Hassan, Syed Ahmad Helmi (2004)
This paper gives a review of Problem-Based Learning (PBL) applied in engineering courses worldwide, and a survey of academic staff who have implemented PBL in engineering classes in Universiti Teknologi Malaysia. The review of PBL application illustrates the extent of acceptance and success of PBL in schools of engineering in the international arena. The survey, on the other hand, illustrates the acceptance of PBL among engineering lecturers and the possibility of applying PBL in Malaysia. The main purpose of the survey is to obtain feedback on PBL regarding the impressions, set-backs and constraints faced, as well as innovations and tips for successful implementation from the faculty members involved.